2010
DOI: 10.1161/circulationaha.109.881003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rosiglitazone on Progression of Coronary Atherosclerosis in Patients With Type 2 Diabetes Mellitus and Coronary Artery Disease

Abstract: the APPROACH Study GroupBackground-Rosiglitazone has several properties that may affect progression of atherosclerosis. The Assessment on the Prevention of Progression by Rosiglitazone on Atherosclerosis in Diabetes Patients With Cardiovascular History (APPROACH) study was undertaken to determine the effect of the thiazolidinedione rosiglitazone on coronary atherosclerosis as assessed by intravascular ultrasound compared with the sulfonylurea glipizide. Methods and Results-This was a randomized, double-blind, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…14,15 The other 14 longterm RCTs (Table 1), including A Diabetes Outcome Progression trial (ADOPT, n = 4360), 32,33 also indicate that SUs were not associated with an increase in CVD risk when compared head-to-head trial with thiazolidinediones (glitazones), DPP-4 inhibitors, metformin or glucagon-like peptide-1 (GLP-1) analogues. [26][27][28][32][33][34][35][36][37][38] The same lack of an adverse outcome was observed when SUs were used as part of a treatment strategy to obtain different glycaemic targets, [14][15][16][17][18][19][39][40][41][42] including the ADVANCE (n = 11,140). 17 However, it must be noted that none of the studies targeting 'similar level' of glycaemic control in the treatment arms were powered to demonstrate CV safety/benefits, and there were inconsistencies in how the CVD events were reported and adjudicated.…”
Section: Impact Of Sus On Cvd Events In Randomized Controlled Trialsmentioning
confidence: 85%
See 1 more Smart Citation
“…14,15 The other 14 longterm RCTs (Table 1), including A Diabetes Outcome Progression trial (ADOPT, n = 4360), 32,33 also indicate that SUs were not associated with an increase in CVD risk when compared head-to-head trial with thiazolidinediones (glitazones), DPP-4 inhibitors, metformin or glucagon-like peptide-1 (GLP-1) analogues. [26][27][28][32][33][34][35][36][37][38] The same lack of an adverse outcome was observed when SUs were used as part of a treatment strategy to obtain different glycaemic targets, [14][15][16][17][18][19][39][40][41][42] including the ADVANCE (n = 11,140). 17 However, it must be noted that none of the studies targeting 'similar level' of glycaemic control in the treatment arms were powered to demonstrate CV safety/benefits, and there were inconsistencies in how the CVD events were reported and adjudicated.…”
Section: Impact Of Sus On Cvd Events In Randomized Controlled Trialsmentioning
confidence: 85%
“…23,24 To date, the large CV outcome trials have essentially assessed the impact of multiple combinations of glucose-lowering agents as part of an overall treatment regimen (e.g. UKPDS, ACCORD 28 ]. Thus, a comparative understanding of the CV impact of the most widely used diabetes drugs is for the most part lacking.…”
Section: Impact Of Specific Diabetes Therapies On Cvd Riskmentioning
confidence: 99%
“…18 In these patients, impaired endothelial function may be attributed to a combination of factors, such as long duration of T2DM with poor glycaemic control and insulin resistance, uncontrolled dyslipidaemia and hypertension, 21 but also to the role of exogenous insulin administration, which has been suggested to exert controversial actions on vessels. [21][22][23] In addition, most studies on carotid intima-media thickness, an index of subclinical structural atherosclerosis, [24][25][26] and a recent study on coronary atherosclerosis assessed by intravascular ultrasound 27 have not shown encouraging results with rosiglitazone in T2DM patients. Thus, a relatively small improvement in severely affected FMD, induced by a low-dose regime of rosiglitazone, without a parallel control of other cardiovascular risk factors and a demonstrable benefit on structural indices of atherosclerosis, may not be sufficient to cause a concomitant improvement in cardiovascular prognosis in patients with advanced T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Recently the APPROACH Study (19) was released, a trial designed to assess the effect of rosiglitazone on coronary atherosclerosis progression compared to glipizide. The primary endpoint was change in percent atheroma volume in the longest and least angulated epicardial coronary artery that had not undergone intervention in patients with an established cardiovascular history.…”
Section: Discussionmentioning
confidence: 99%